On the intersystem crossing rate in a Platinum(ii) donor–bridge–acceptor triad. Issue 38 (28th September 2021) - Farrow, G. A.; Quick, M.; Kovalenko, S. A.; Wu, G.; Sadler, A.; Chekulaev, D.; Chauvet, A. A. P.; Weinstein, J. A.; Ernsting, N. P.
Abstract : A combination of ultrafast broadband fluorescence upconversion spectroscopy and femtosecond stimulated Raman spectroscopy resolves the rates of intersystem crossing in donor–bridge–acceptor complexes. Abstract : The rates of ultrafast intersystem crossing in acceptor–bridge–donor molecules centered on Pt(ii ) acetylides are investigated. Specifically, a Pt(ii ) trans -acetylide triad NAP––Pt––Ph-CH2 -PTZ [1 ], with acceptor 4-ethynyl- N -octyl-1, 8-naphthalimide (NAP) and donor phenothiazine (PTZ), is examined in detail. We have previously shown that optical excitation in [1 ] leads to a manifold of singlet charge-transfer states, S*, which evolve via a triplet charge-transfer manifold into a triplet state 3 NAP centered on the acceptor ligand and partly to a charge-separated state 3 CSS (NAP − –Pt–PTZ + ). A complex cascade of electron transfer processes was observed, but intersystem crossing (ISC) rates were not explicitly resolved due to lack of spin selectivity of most ultrafast spectroscopies. Here we revisit the question of ISC with a combination and complementary analysis of (i) transient absorption, (ii) ultrafast broadband fluorescence upconversion, FLUP, which is only sensitive to emissive states, and (iii) femtosecond stimulated Raman spectroscopy, FSR. Raman resonance conditions allow us to observe S* and 3 NAP exclusively by FSR, through vibrations which are pertinent only to these two states. This combination of methods enabled us to extract the intersystem crossing rates that were not previously accessible. Multiple timescales (1.6 ps to ∼20 ps) are associated with the rise of triplet species, which can now be assigned conclusively to multiple ISC pathways from a manifold of hot charge-transfer singlet states. The analysis is consistent with previous transient infrared spectroscopy data. A similar rate of ISC, up to 20 ps, is observed in the trans -acetylide NAP––Pt––Ph [2 ] which maintains two acetylide groups across the platinum center but lacks a donor unit, whilst removal of one acetylide group in mono-acetylide NAP––Pt–Cl [3 ] leads to >10-fold deceleration of the intersystem crossing process. Our work provides insight on the intersystem crossing dynamics of the organo-metallic complexes, and identifies a general method based on complementary ultrafast spectroscopies to disentangle complex spin, electronic and vibrational processes following photoexcitation.